Drawing close to God: Malay perspective of the pilgrimage - Sharifah Zaleha Syed Hassan (Universiti Kebangsaan Malaysia, 2002)
Muslim pilgrims the world over observe the same rules when performing the hajj but attach different allegorical meanings to the ritual depending on how local beliefs and understanding of Islamic myths are built into the ritual. Drawing on stories concerning the trials that God imposed on Prophet Ibrahim to abandon his wife, Hajar, and later, to sacrifice his son, Ismail, Malay pilgrims see in the hajj a means to achieve transformation for the better in terms of character, wisdom and individual piety. Throughout the haj process, a Malay pilgrim attempts to transcend his body and base desires so the heart stays focus on Allah. The main emotional work for him is to channel his fear and anxiety into a sense of determination so he can empathise with the missions and experiences of past prophets and be eternally grateful to Allah. Thus, the goal of the hajj to the Malays is not to acquire power or material benefits but a special experience which produces a stream of religious consciousness to allow them to come to grips with their inner conflict as well as recognise the integrative function of the values of equality, humbleness, perseverance and selflessness that Islam strongly upholds